Photochromic Fentanyl Derivatives for Controlled mu-Opioid Receptor Activation - Lahmy, Ranit; Hübner, Harald; Schmidt, Maximilian; Lachmann, Daniel; Gmeiner, Peter; König, Burkhard (Chemistry - A European Journal, 2022)
Photoswitchable ligands as biological tools provide an opportunity to explore the kinetics and dynamics of the clinically relevant mu-opioid receptor. These ligands can potentially activate or deactivate the receptor when desired by using light. Spatial and temporal control of biological activity allows for application in a diverse range of biological investigations. Photoswitchable ligands have been developed in this work, modelled on the known agonist fentanyl, with the aim of expanding the current "toolbox" of fentanyl photoswitchable ligands. In doing so, ligands have been developed that change geometry (isomerize) upon exposure to light, with varying photophysical and biochemical properties. This variation in properties could be valuable in further studying the functional significance of the mu-opioid receptor.
CRIS-Team WoS Importer:2022-09-23